2022
DOI: 10.3390/f13060958
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Microbial Community and Carbon Flux Regime across a Subtropical Montane Peatland-to-Forest Successional Series in Taiwan

Abstract: Subtropical montane peatland is among several rare ecosystems that continue to receive insufficient scientific exploration. We analyzed the vegetation types and soil bacterial composition, as well as surface carbon dioxide and methane fluxes along a successional peatland-to-upland-forest series in one such ecosystem in Taiwan. The Yuanyang Lake (YYL) study site is characterized by low temperature, high precipitation, prevailing fog, and acidic soil, which are typical conditions for the surrounding dominant Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…We speculated that the root endophytes of P. hysterophorus have a particular specificity. Previous studies showed that Acidobacteriota was well-adapted to low-nutrient environments [ 24 ], representing a highly diverse phylum resident to a wide range of habitats around the globe [ 25 ]. In addition, Acidobacteriota was involved in using nitrite as the N source, responding to the soil, expressing multiple active transporters, degrading gellan gum, and producing exopolysaccharides [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that the root endophytes of P. hysterophorus have a particular specificity. Previous studies showed that Acidobacteriota was well-adapted to low-nutrient environments [ 24 ], representing a highly diverse phylum resident to a wide range of habitats around the globe [ 25 ]. In addition, Acidobacteriota was involved in using nitrite as the N source, responding to the soil, expressing multiple active transporters, degrading gellan gum, and producing exopolysaccharides [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major operational taxonomic units (OTUs) identified in this study are associated with bacterial communities of Acidobacteriota, Proteobacteria, Actinobacteria, and the archaeal communities of Thermoplasmata and Crenarchaeota. The most dominant phyla were Acidobacteriota and Proteobacteria which appear widely in most peatland ecosystems (Williams and Crawford, 1983;Kanokratana et al, 2011;Lin et al, 2012;Tsitko et al, 2014;Tripathi et al, 2016;Urbanová and Bárta, 2016;Espenberg et al, 2018;Too et al, 2018;Dom et al, 2021;Chen et al, 2022). Acidobacteriota has a diverse set of transporters for absorbing various substrates and can adapt to organic-rich oligotrophic conditions with low nutrients and pH (Lin et al, 2011;Trivedi et al, 2016;Zhang et al, 2016).…”
Section: Microbial Abundance In Peat Swamp Forest and Oil Palm Planta...mentioning
confidence: 99%